Improvement in mechanical properties of hypereutectic Al-Si-Cu alloys through sono-solidified - Yoshiki Tsunekawa; Shinpei Suetsugu; Masahiro Okumiya (China Foundry, 2014)
For the wider applications, it is necessary to improve the ductility as well as the strength and wear-resistance of hypereutectic Al-Si-Cu alloys, which are typical light-weight wear-resistant materials. An increase in the amounts of primary silicon particles causes the modified wear-resistance of hypereutectic Al-Si-Cu alloys, but leads to the poor strength and ductility. It is known that dual phase steels composed of hetero-structure have succeeded in bringing contradictory mechanical properties of high strength and ductility concurrently. In order to apply the idea of hetero-structure to hypereutectic Al-Si-Cu alloys for the achievement of high strength and ductility along with wear resistance, ultrasonic irradiation of the molten metal during the solidification, which is called sono-solidification, was carried out from its molten state to just above the eutectic temperature. The sono-solidified Al-17Si-4Cu alloy is composed of hetero-structure, which are, hard primary silicon particles, soft non-equilibrium a -Al phase and the eutectic region. Rheo-casting was performed at just above the eutectic temperature with sono-solidified slurry to shape a disk specimen. After the rheo-casting with modified sonosolidified slurry held for 45 s at 570 篊, the quantitative optical microscope observation exhibits that the microstructure is composed of 18area% of hard primary silicon particles and 57area% of soft a -Al phase. In contrast, there exist only 5 area% of primary silicon particles and no a -Al phase in rheo-cast specimen with normally solidified slurry. Hence the tensile tests of T6 treated rheo-cast specimens with modified sono-solidified slurry exhibit improved strength and 5% of elongation, regardless of having more than 3 times higher amounts of primary silicon particles compared to that of rheo-cast specimen with normally solidified slurry.